Steady-state fusion fission reactor concepts based on stellarator-mirror and mirror machines - Ågren, O.; Moiseenko, V.E.; Noack, K.; Chernitskiy, S.V. (Вопросы атомной науки и техники, 2015)
Neutron sources and hybrid reactors offer a possibility for application of fusion in a not too distant future. Steady-state operation on a time scale of a year without interruption is essential for such applications. In response to this need, our studies are focused on concepts which are not limited by pulsed operation. Special attention is put on mirror machines and a stellarator-mirror concept with localized neutron production. Reactor safety, magnetic coils, power amplification by fission, plasma heating, a radial constant of motion which provides a bounded radial motion in the collision free approximation are some of the issues addressed.